INFLUENCE OF ENVIRONMENTAL FACTORS ON INFLORESCENCE PRODUCTION IN Vanilla pompona CULTIVATION SYSTEMS IN THE TINGANA CONSERVATION CONCESSION, MOYOBAMBA, PERU - Mario Edinson Chinchay Carrasco; Miguel Tomás Guerra Saldaña; Jhon Jairo López Rojas (Tropical and Subtropical Agroecosystems)
Background. Vanilla is a crop of great economic and sociocultural importance, due to the relevance of compounds such as vanillin, which is used in the production of pharmaceutical, cosmetic and food products. Low inflorescence production is a frequent problem that is related to adverse environmental factors in cultivation systems, affecting the production of this edible orchid. Objective. To evaluate the influence of environmental factors on inflorescence production in cultivation systems of Vainilla pompona in the Tingana Conservation Concession, Moyobamba, Peru. Methodology. Every two weeks, between June and September 2023, V. pompona inflorescence production was recorded and environmental conditions (temperature, relative humidity and luminosity) were monitored in three different cultivation systems: raschel mesh (RM), secondary forest (SF) and forest plantation (FP). The analysis of covariance (ANCOVA) was used to determine the influence of environmental factors on inflorescence production, considering the months of study and cultivation systems as fixed factors and temperature, relative humidity and luminosity as covariates. Results. August was the month that presented higher average values of temperature (between 22.8±0.9 and 24.1±1.2 °C) and luminosity (between 49877.8±12746.4 and 97341.5±27413.3 Lux), and lower relative humidity (between 78.8±4.4 and 84.9±4.1 %). FP recorded higher temperature (24.1±1.2 °C) and lower relative humidity (78.8±4.4 %) than SF and RM, where environmental factors were relatively similar with a slight increase in SF. There was higher inflorescence production in SF (n = 44), followed by FP (n = 40) and RM (n = 36), with July being the month of highest production in all three cropping systems. Inflorescence production varied between study months and not between cropping systems. Temperature and luminosity had significant effects on inflorescence development and relative humidity did not influence the variable. During July, environmental conditions were optimal for inflorescence production in the three cropping systems, with SF being the one with the highest production. Implications. Farmers in the Tingana Conservation Concession may choose to grow V. pompona in SF, as it presents more favorable environmental conditions and it is advisable to develop pruning practices in RM to promote optimal conditions. Conclusions. Temperature and luminosity are important environmental factors for the development of V. pompona inflorescences in the Tingana Conservation Concession.